Adding value of the Charlson comorbidity index to the Grace score for mortality risk prediction in patients with acute coronary syndrome. (3rd May 2023) - Campanile, A; Prota, C; Tedeschi, M; Giano, A; Pianese, B; Cristiano, M; Pompa, A; Sorrentino, R; Vigorito, F; Ravera, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The Global Registry of Acute Coronary Events (GRACE) risk score is widely recommended for risk assessment in patients with acute coronary syndrome (ACS). The Charlson Comorbidity Index (CCI) is a recognized measure of comorbid burden, and a useful tool for estimating prognosis in patients with multiple coexisting illnesses. Despite it has been validated in the context of ACS-related mortality, scarce and conflicting data still exist about the role of the CCI when added to the traditional GRACE risk score for outcome prediction in patients with acute coronary syndrome (ACS). Purpose: The assessment of the potential predictive value of the CCI both for short, and long term all-cause mortality, in a contemporary ACS population, and its potential adding value beyond the GRACE risk score. Methods: All consecutive admission due to ST-elevation myocardial infarction-STEMI, non ST elevated myocardial infarction-NSTEMI, and unstable angina-UA, from 01/01/2018 to 31/12/2020 were retrospectively reviewed from an internal database of a tertiary cardiac center in Italy. Logistic and Cox proportional regression analysis were performed in order to assess the contribution of the CCI on short and long term mortality. In order to specify the CCI adding value to the GRACE score, several measures of improvement in discrimination (increase in the area under the receiver-operating characteristic curve-AUC, the integrated discrimination improvement-IDI, and the continuous net reclassification improvement-cNRI>0), were implemented. Robustness of the results were assessed through an internal validation procedure with bootstrapping. Results: A total of 1310 patients (646 STEMI, 588 NSTEMI, and 76 UA) were identified. Almost 28% were female, and the median age was 68 (58-78). 97 (7, 4%) and 136 (11, 2%) deaths occurred, respectively, in hospital and during long term follow-up (median follow-up time: 12 months; IQR: 8-23). After multivariate logistic regression analysis the CCI was not associated with in-hospital death, while it was significantly and independently associated with the long-term mortality along with GRACE score (HR: 1, 33, 95% CI: 1, 22-1, 43; p<0, 001, Fig.1). An additive effect of CCI with the GRACE risk score was observed in predicting long-term mortality with an AUC from 0, 762 to 0.821 (p < 0, 001). The incremental predictive value of combining CCI and the GRACE risk score for the long term mortality was significantly improved, as shown by the net reclassification improvement (cNRI>0: 0.678, p < 0.001, Table 1) and integrated discrimination improvement (IDI: 0.08, p < 0.001). Conclusion: The CCI is a predictor of long-term mortality and improves risk stratification of patients with ACS over the GRACE risk score. Fig.1 Table 1